The desk reference of statistical quality methods - Crossley, Mark L., 1941- (ASQ Quality Press, 2008)
This is an excellent reference book for quality practitioners, providing quick reference and stand-alone topics in alphabetical order. Detailed computational steps are incorporated throughout the work along with very helpful presentations on how to use quality techniques and tools.
Keywords: Quality control -- Statistical methods.; Process control -- Statistical methods.; elektronické knihy; electronic books